Extraction and Preconcentration of Pd(II) by Dispersive Liquid Liquid Microextraction from different real samples and Determination by Spectrophotometry Uv-Vis - raziyeh ashtary; shahla elhami (شیمی کاربردی روز, 2017)
This article presents new and sensitive method for the determination of trace amounts of Palladium (II) by dispersive liquid–liquid microextraction(DLLME) combined with UV–vis spectrophotometry. The method is based on the complex formation of Pd(II) with Eriochrom cyanine R and using chloroform as extraction solvent. Cetyl Trimethyl ammonium Bromide(CTAB) was used as disperser agent. The effective parameters such as solution pH, concentration of Eriochrom cyanine R, type and volume of extraction solvent, concentration of CTAB and time of centrifuge were investigated and optimized. The method yields a linear calibration curve in the concentration range of 0.050–1.600 µg mL -1 of Pd(II), and the limit of detection is 0.008 µg mL-1. The relative standard deviations for eight replicate determinations of 0.100 and 1.000 µg mL-1 of Pd(II) were 3.7 % and 1.4%, respectively. The proposed method was successfully applied to preconcentration and determination of Pd(II) in tea, soil and water samples.